Requirements For the Introduction of Artificial Intelligence Technology in Teaching Kuwaiti Universities Students from The Point of View of Faculty Members - Al-Slehat, Rawan Yousef; Flouh, Rawan Fayyad; Almutairi, Nayef Lafi; Al-Baher, Ibrahim; Joma, Ahlam Jameel (Technium Social Sciences Journal, 2023)
The study aims to identify the requirements for the introduction of artificial intelligence technology in the teaching of teaching Kuwaiti universities students from the point of view of faculty members. (28) paragraphs and the sample consisted of (149) faculty members in teaching Kuwaiti universities, and the results showed that the study sample agreed with the requirements for introducing artificial intelligence technology in teaching university students with a degree (I agree), and the results showed statistically significant differences for the requirements for introducing Artificial intelligence technology in teaching university students is due to the variable of gender and years of experience. The most important recommendation of the study came to the need to develop the educational environment in teaching Kuwaiti universities to provide requirements for the introduction of artificial intelligence technology in the educational process in teaching Kuwaiti universities to keep pace with global developments.